دور التمويل الأصغر الإسلامي في معالجة البطالة في اليمن دراسة تطبيقية عن اليمن - Alrashedi, Mohammed Yahya; Mohamed, Mustafa Omar; Othman, Anwar Hasan Abdullah (Islamic economy platform, 2021)
Islamic microfinance in Yemen, faces many challenges that undermine its vital role. Therefore it was necessary to continue to evaluate and develop it. Therefore, this paper aimed to assess the role of Islamic microfinance institutions in reducing the unemployment rate through the development of micro-entrepreneurship. It also aimed to propose Waqf, zakat, and crowdfunding as sustainable sources of financing Islamic microfinance institutions. To achieve the objectives of this study, the researcher used the quantitative and qualitative approach, whereby questionnaires were distributed to clients of Islamic microfinance institutions in Sana'a, The study revealed that Islamic microfinance institutions have a significant impact on micro-entrepreneurship in Yemen. It found that microentrepreneurship has a negative impact on the unemployment rate in Yemen. It also revealed that the sources of waqf, zakat, and crowdfunding will have a great impact on the development of Islamic microfinance institutions in Yemen. Moreover, the findings of the study therefore provide guidance for policymakers and microfinance institutions as well as the microenterprises to develop and improve their business activities.